Study of surgical management of fracture of proximal humerus by PHILOS plate and screws - Seetharam, Channappa T.; Jayaram, Manju; Bachhappa, Shivakumar H.; Ramalingaiah, Yatish; Hadi, Syed Abdul (International Journal of Research in Orthopaedics, 2020)
Background: Proximal humerus fracture accounts for about 5% of all fractures in recent advances proximal humerus fractures are often managed operatively with PHILOS plate which provides greater angular stability and study was aimed at to assess functional outcome of PHILOS plate fixation in proximal humerus fractures. Methods: Prospective study of 31 cases of proximal humerus fractures admitted and operated in Kempegowda Institute of Medical Sciences Hospital November 2017 to May 2019 of which 4 patients died due to medical comorbidities so 27 patients were studied. Follow-up of these patients was done at 6 weeks, 12 weeks and 24 weeks with functional evaluation was done using Constant and Murley (CM) scoring and disabilities of the arm, shoulder and hand (DASH) scoring. Results: CM scoring and DASH scoring was applied to analyze the functional outcome among the cases. Most of the patients had excellent outcome (52%) followed by good (26%), fair (8%) and poor (15%) outcome according to CM scoring and according to DASH scoring 20.21 was mean score and mean CM score was 77.62. Complications observed were impingement in 1 patient, avascular necrosis in 2 patient and non union in 1 case. Conclusions: We conclude that the use of PHILOS plate for the fixation of proximal humerus fractures is a good device as it provides rigid fixation and early mobilisation and prevented complications. Precontoured locking plates work on the principle of angular stability, divergent screws, less disruption of vascularity and less chances of plate failure.